Determinants of foreign direct investment flow in Malaysia / Muhammad Firdhaus Md Isa - Md Isa, Muhammad Firdhaus (2022)
The Purpose of this research is to examine the sustainability of economic factors make a significant impact to the Foreign Direct Investment (FDI) into Malaysia. The issues of FDI have concern much since it is already make movement start investing into the abroad company instead stay made invest in Malaysian. This problem become more serious for economy growth in Malaysia since COVID-19 pandemic. Besides, the financial issue in Malaysia effect the FDI. FDI increase will cause the economic growth in our country. In this study, the research examines the long-run relationship between Foreign Direct Investment (FDI), Unemployment Rate, Stocks Traded, Manufacturing, Inflation Rate and Market Size. The secondary data collected for this research were from information on company's related to databases of World Bank, Humanitarian Data Exchange and World Development Indicators between the year 1990 to 2019. The purpose of running this research is to focus on descriptive analysis, correlation and regression. From the finding we can see only unemployment, stocks traded and market size is significant in this study, meanwhile the other two variables; manufacturing and inflation rate is not significant.